Who can blame who for what and how in responsibility for health? - Snelling, Paul C. (Nursing philosophy, 2015)
This paper starts by introducing a tripartite conception of responsibility for health consisting of a moral agent having moral responsibilities and being held responsible, that is blamed, for failing to meet them and proceeds to a brief discussion of the nature of the blame, noting difficulties in agency and obligation when the concept is applied to health-threatening behaviours. Insights about the obligations that we hold people to and the extent of their moral agency are revealed by interrogating our blaming behavior, and to facilitate this, my own blaming attitudes and actions are analysed in respect of an imagined adult son who seeks thrills by jumping from a pier into the sea, an activity common around coastlines and intended to be analogous in varying degrees to a range of health-threatening behaviours. I consider my responses to this imagined act in relation to some features of moralism, the excess of morality, concluding that blame can be justified when it is proportionate and within interpersonal relationships. There is evidence that some nurses hold negative blaming attitudes towards groups of patients considered to have caused or contributed to their illness, but this is not justified, not only because of impaired agency, but also because if there is responsibility for health, associated obligations are owed to those who share our lives, and it is those people who are entitled to hold individuals responsible. Nurses who hold negative blaming attitudes towards groups of patients are invited to identify the status of moral agency, the precise natures of their (failed) obligations, and of the patient-nurse relationship. It is concluded that reflection on these matters and the difference between justified blame and moralism demonstrates that blaming behaviour in the context of professional health care is built on nothing stronger than prejudice.